Activation of SO2 with [(η5‐C5Me5)2Ln(THF)2] (Ln=Eu, Yb) Leading to Dithionite and Sulfinate Complexes. Issue 42 (4th September 2014) - Klementyeva, Svetlana V.; Gamer, Michael T.; Schmidt, Anna‐Corina; Meyer, Karsten; Konchenko, Sergey N.; Roesky, Peter W.
Abstract The reaction of decamethylytterbocene [(η5‐C5Me5)2Yb(THF)2] with SO2 at low temperature gave two new compounds, namely, the YbIII dithionite/sulfinate complex [(η5‐C5Me5)2Yb(μ3, 1κ2O1, 3, 2κ3O2, 2′, 4‐S2O4)2(η5‐C5Me5)Yb(μ, 1κO, 2κO′‐C5Me5SO2)2] (1) and the YbIII dithionite complex [(η5‐C5Me5)2Yb2(μ, 1κ2O1, 3, 2κ2O2, 4‐S2O4)] (2). After extraction of 1, the mixture was heated to give the dinuclear tetrasulfinate complex [(η5‐C5Me5)Yb2(μ, κO, κO'‐C5Me5SO2)4] (3 a). In contrast, from the reaction of [(η5‐C5Me5)2Eu(THF)2] with SO2 only the tetrasulfinate complex [(η5‐C5Me5)Eu2(μ, κO, κO'‐C5Me5SO2)4] (3 b) was isolated. Two major reaction pathways were observed: 1) reductive coupling of two SO2 molecules to form the dithionite anion S2O42−; and 2) nucleophilic attack of one metallocene C5Me5 ligand on the sulfur atom of SO2. The compounds presented are the first dithionite and sulfinate complexes of the f‐elements.